Retrospective physical dosimetry in the Czech Republic: an overview of already established methods and recent research. (4th May 2022) - Ekendahl, Daniela; Čemusová, Zina; Reimitz, Dan; Vávra, Jakub
Abstract: Purpose: The threat of serious radiation exposures to members of the public from radiological incidents and nuclear events has led to intensive study of a number of emergency dosimetry techniques for purposes of triage. As such, a national laboratory of retrospective dosimetry was established in our institute. The purpose of this work is to provide a summary of the well-established and already implemented retrospective physical dosimetry techniques based on thermoluminescence (TL), optically stimulated luminescence (OSL) and neutron activation including their specifics. Moreover, we present some new results of the experimental work, in which we compared dosimetry potential of various dental repair materials and human teeth. Materials and methods: At first, an overview of already established retrospective physical retrospective methods including their main features was compiled. As regards recent research, an experimental comparative study was performed under defined conditions. The materials used were aliquots prepared from both pure and repaired teeth and aliquots of unused dental ceramics of known type. Following irradiation, we compared TL and OSL curves of the materials. We also compared dosimetry characteristics of OSL signal as reproducibility, dose dependence and fading. Results: After irradiation, the teeth aliquots of dental enamel and dentin exhibited very low OSL and TL signals compared with aliquots containing some dental repair materials or aliquots of pure dental ceramics. With a few exceptions, the OSL signal of dental enamel and dentin aliquots irradiated to 2 Gy was hardly distinguishable from OSL signal corresponding to unirradiated aliquots. In contrast, aliquots of teeth containing some dental repair material and aliquots of pure dental ceramics provided a well reproducible OSL signal exhibiting linear dose response. All the materials tested exhibited a significant fading of the OSL signal. The loss of OSL signal during the first 24 hours after irradiation was from 20 to 99% of its original value obtained immediately after the irradiation. Conclusions: The already established physical methods of retrospective dosimetry use a spectrum of verified materials and techniques for dose assessment in the aftermath of serious radiological incidents and nuclear events. In the comparative study, we found that the dosimetry potential of teeth in natural state is much worse compared to teeth repaired with dental ceramics or dental cement fillings. Teeth restored with dental repair materials exhibited relatively favorable dosimetry characteristics. However, they can be usable for a dose reconstruction only on condition that the main practical problems connected with fading and optical bleaching were solved.